Programmes of help to perpetrators of domestic violence - experience and attitudes in the Czech Republic - Šímová, Ivana; Zimmelová, Petra (Journal of Nursing, Social Studies and Public Health, 2012)
The article tries to react to a very current issue of help to perpetrators of domestic violence. Most organisations in the Czech Republic focus only on help to victims of domestic violence. The possibility of providing help to perpetrators of domestic violence still remains to be an unexplored area. Thus, the aim of the research was to map organisations in the Czech Republic that could provide such help, to find out what experience with perpetrators of domestic violence these organisations have had up to now, and what is their attitude to such help. The research results showed that help provided to perpetrators of domestic violence is considered to be a necessary part of domestic violence prevention. A number of organisations that could provide help to perpetrators of domestic violence were found. Most of these organisations were found in the South-Moravian and Central- Bohemian Regions, fewest of them were found in the Olomouc Region. Advisory centres for family, marriage and interpersonal relations and marriage and family advisory centres were the organisations that had most experience with perpetrators of domestic violence. These organisations were able to provide most social-legal and psychological consultancy within their competencies. Despite their above-mentioned experience with perpetrators of domestic violence most of them support the idea of establishing special workplaces that would focus only on work with this specific group of people. What seems to be the most problematic matter is especially the fact that the system of help to perpetrators of domestic violence in the Czech Republic is not controlled and consistent enough.
Keywords: Česká republika; Organizations, Nonprofit; domácí násilí; Czech Republic; Social Work; lidé; Surveys and Questionnaires; sociální práce; Humans; Domestic Violence; průzkumy a dotazníky; neziskové organizace